2014
DOI: 10.1016/j.ijrobp.2013.10.037
|View full text |Cite
|
Sign up to set email alerts
|

A Nonhuman Primate Model of Human Radiation-Induced Venocclusive Liver Disease and Hepatocyte Injury

Abstract: Background Human liver has an unusual sensitivity to radiation that limits its use in cancer therapy or in preconditioning for hepatocyte transplantation. Since the characteristic venocclusive lesions of radiation-induced liver disease do not occur in rodents, there has been no experimental model to investigate the limits of safe radiation therapy or explore the pathogenesis of hepatic venocclusive disease. Methods We performed a dose escalation study in a primate, the cynomolgus monkey, using hypofractionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Having previously established the liver’s sensitivity to irradiation in cynomolgus monkeys through dose escalation studies, we selected a radiation dose of 10Gy, well below the threshold for liver or systemic toxicity [17]. Three-dimensional CT-based treatment planning was performed for delivery of intensity modulated radiation therapy to the right lobe of the liver.…”
Section: Resultsmentioning
confidence: 99%
“…Having previously established the liver’s sensitivity to irradiation in cynomolgus monkeys through dose escalation studies, we selected a radiation dose of 10Gy, well below the threshold for liver or systemic toxicity [17]. Three-dimensional CT-based treatment planning was performed for delivery of intensity modulated radiation therapy to the right lobe of the liver.…”
Section: Resultsmentioning
confidence: 99%
“…Recent technological advances in radiation therapy have sparked renewed interest in understanding radiationinduced liver disease (RILD) 44 Although whole-liver irradiation has generally been restricted to [30][31][32][33][34][35] Gy in standard daily fractions of 1.8-2.0 Gy owing to risk of lethal RILD above these levels, intensity-modulated radiation therapy, 3-dimensional conformal radiation treatment planning, and organ and tumor motion tracking enable treatment of liver cancer with fewer but larger dose fractions. 45 This innovation is called "hypofractionated stereotactic body RT".…”
Section: Experimental Investigation In Animalsmentioning
confidence: 99%
“…45 This innovation is called "hypofractionated stereotactic body RT". Returning to the original Cynomolgus monkey model of RILD, 26 Yannam et al 44 recently conducted an escalated dose study to examine the effect of newer hypofractionated regimes on the liver. The authors demonstrated a higher tolerance for hypofractionated radiation, but that the characteristic histological lesions of SOS still developed at radiation doses above 40 Gy.…”
Section: Experimental Investigation In Animalsmentioning
confidence: 99%
“…The effects of radiation exposure on stem cells (Adler and Erbelding 1988), brain electrical activity (Legeza and Turlakov 1991), liver function (Yannam et al 2014), clinical, cardiac, cortisol stress response (Darenskaia et al 1992, 2001), and mitigating effects of gonadotropin hormone releasing hormone (GnRH) antagonism on the testes (Shetty et al 2013) have been studied in this species. Additional studies focusing on immune tissues/organs in this species should facilitate identification of pathways to immune dysfunction and hypothesis generation leading to novel pharmacologic and/or nutritional countermeasures to prevent or treat adverse effects of radiation on at risk organ systems.…”
Section: Discussionmentioning
confidence: 99%